2017
DOI: 10.1038/s41598-017-08709-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer size silicon particles for hyperpolarized MRI

Abstract: Hyperpolarized silicon particles have been shown to exhibit long spin-lattice relaxation times at room temperature, making them interesting as novel MRI probes. Demonstrations of hyperpolarized silicon particle imaging have focused on large micron size particles (average particle size (APS) = 2.2 μm) as they have, to date, demonstrated much larger polarizations than nanoparticles. We show that also much smaller silicon-29 particles (APS = 55 ± 12 nm) can be hyperpolarized with superior properties. A maximum po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 41 publications
(42 reference statements)
2
45
0
Order By: Relevance
“…The room‐temperature decay of 29 Si magnetization was monitored for the sample (following 16.5 hours of DNP), and exhibited a T 1 value of ∼25 minutes (Figure c). This T 1 is in line with expectations for other (non‐porous) silicon particles which are polarized without utilizing radicals,, and is significantly longer than what is typically afforded by hyperpolarized imaging agents (for example, 13 C‐pyruvate T 1 ∼60 seconds, 15 N‐TMPA(trimethylpheny‐lammonium) T 1 ∼1128 seconds, 89 Y‐(DOTA) T 1 ∼499 seconds). This long relaxation time constant allows high resolution 29 Si MR imaging of the silicon particles within the sample tube up to 40 minutes after removal from the DNP device (Figure d).…”
Section: Figuresupporting
confidence: 81%
“…The room‐temperature decay of 29 Si magnetization was monitored for the sample (following 16.5 hours of DNP), and exhibited a T 1 value of ∼25 minutes (Figure c). This T 1 is in line with expectations for other (non‐porous) silicon particles which are polarized without utilizing radicals,, and is significantly longer than what is typically afforded by hyperpolarized imaging agents (for example, 13 C‐pyruvate T 1 ∼60 seconds, 15 N‐TMPA(trimethylpheny‐lammonium) T 1 ∼1128 seconds, 89 Y‐(DOTA) T 1 ∼499 seconds). This long relaxation time constant allows high resolution 29 Si MR imaging of the silicon particles within the sample tube up to 40 minutes after removal from the DNP device (Figure d).…”
Section: Figuresupporting
confidence: 81%
“…In particular, crystalline silicon in the form of micro-and nanoparticles can be used as a background-free MRI contrast agent. [11][12][13][14][15] As such, direct MR detection of hyperpolarized micro-and nanoparticles based on crystalline silicon has shown promising results, with the possibility of signal detection beyond one hour after administration of the particles, which is much longer than any times reported for other hyperpolarized biomolecular probes 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Conducting the DNP process at higher magnetic fields is also expected to increase final Micrometer-sized Si MPs, which reveal the longest known relaxation times up to 136 min at room temperature at 2.9 T [20], are difficult to administer and impossible to handle in-vivo. A new window for MRI applications was opened in Reference [52], where it was demonstrated that 29 Si NPs in powder synthesized from a gas phase using a laser-assisted technique, with average particle size of 55 ± 12 nm can be hyperpolarized with superior properties, that is, maximal polarization about 12.6% with a long T 1 relaxation time of 42.3 ± 0.1 min at room temperature ( Figure 19A). Such a long depolarization time enabled the observation of 29 Si NMR signal more than 5 h after transfer to the imaging system ( Figure 19B,C).…”
Section: In Vivo Mri Of Hyperpolarized Si Particlesmentioning
confidence: 99%
“…The Fourier-transformed free induction decay signal acquired at t = 1 min (B) and t = 5.2 h (C) at room temperature using a 9.4 T imaging system. (Reprinted from Reference[52], © (2017), Springer Nature. This article is licensed under a Creative Commons Attribution 4.0 International License http://creativecommons.org/licenses/by/4.0/).…”
mentioning
confidence: 99%